Tell me everything : a novel [large type] - Strout, Elizabeth (Center Point Large Print, 2024)
"Elizabeth Strout returns to the town of Crosby, Maine, and to her beloved cast of characters -- Lucy Barton, Olive Kitteridge, Bob Burgess, and more -- as they deal with a shocking crime in their midst, fall in love and yet choose to be apart, and grapple with the question, as Lucy Barton puts it, "What does anyone's life mean?" It's autumn in Maine, and the town lawyer Bob Burgess has become enmeshed in an unfolding murder investigation, defending a lonely, isolated man accused of killing his mother. He has also fallen into a deep and abiding friendship with the acclaimed writer Lucy Barton, who lives down the road in a house by the sea with her ex-husband, William. Together, Lucy and Bob go on walks and talk about their lives, their fears and regrets, and what might have been. Lucy, meanwhile, is finally introduced to the iconic Olive Kitteridge, now living in a retirement community on the edge of town. They spend afternoons together in Olive's apartment, telling each other stories. Stories about people they have known -- "unrecorded lives," Olive calls them -- reanimating them, and, in the process, imbuing their lives with meaning."--